Numerical Solution of Energy Equation in Porous Channels under Effects of Radiation Field - Hammodat, Ala’a A.; Al-Bairaqdar, Osama T.; Hammodat, Abida T. (Iraqi Journal of Science, 2021)
In this paper, we built a mathematical model for convection and thermal radiation heat transfer of fluid flowing through a vertical channel with porous medium under effects of horizontal magnetic field (MF) at the channel. This model represents a 2-dimensional system of non-linear partial differential equations. Then, we solved this system numerically by finite difference methods using Alternating Direction Implicit (ADI) Scheme in two phases (steady state and unsteady state). Moreover, we found the distribution and behaviour of the heat temperature inside the channel and studied the effects of Brinkman number, Reynolds number, and Boltzmann number on the heat temperature behaviour. We solved the system by building a computer program using MATLAB.